Investigation of thyroid function tests and lipid levels in cerebrovascular patients - Çambay, Zafer; Adsiz, Taner; Keser, Serhat; Domaç, Füsun Mayda (Niyazi BULUT, 2024)
Worldwide, cerebrovascular diseases rank third as the cause of death after heart diseases and cancer, and ranks first as the cause of handicap and disability. It is a disease that needs to be well known and recognized, especially due to the high risk of mortality in the acute period and the severe loss of function in the majority of surviving patients, requiring long-term care and assistance. In this study, it is aimed to contribute to the literature and to examine the relationship between thyroid dysfunction and cerebrovascular diseases in patients with hyperlipidemia. When the patient and control groups were evaluated in terms of blood lipid levels, HDL levels were found to be significantly lower in the patient group compared to the control group. VLDL, TG and cholesterol levels were found to be significantly higher in the patient group compared to the control group. The T3 value was found to be statistically significantly lower in the patient group. In some cases such as hyperthyroidism, hypothyroidism and hyperlipidemia, it may not show serious clinical symptoms, which increases the importance of these investigations. We believe that the detected thyroid dysfunction and dyslipidemia treatments will decrease the acute stroke prevalence and improve the prognosis.
Keywords: Classical Physics (Other); Klasik Fizik (Diğer)